CALLUS INITIATION AND PLANT ORGAN REGENERATION OF ARBUTUS ANDRACHNE L. FROM LEAVES AND NODES GROWN FROM IN VITRO SEED CULTURE - SULAIMAN, LOLAV S.; TOMA, RAFAIL S. (Journal of Duhok University, 2023)
A successful attempt was done to overcome the traditional seed germination barriers of Arbutus andrachne L. by applying the tissue culture technique. Seeds were successfully disinfested by NaOCl and ethyl alcohol to produce healthy cultures. Treating with GA3 raised the germination rate from only 17% (control) to 45.7 % and 54.28% by adding 1 mg. l-1 GA3 and 2.5 mg. l-1 BA with and without cold pretreatment. As well as, the above GA3 treatment was very beneficial in increasing the speed of seed germination. For callus induction, the culture of node explants was superior to the culture of leaf discs by reaching 100% as compared to only 66% of leaves. The cultured on WPM with both BA and TDZ respectively records the best callus induction (100%). The best-combined treatment was the culture of nodes on WPM enriched with 1.0 mg.l-1 NAA+ 1.0 mg.l-1 BA by producing the highest callus weight reaching 34.250 g. Finally, interesting organogenesis and regeneration were noticed on the induced callus from both leaf discs and nodes. The best shoot and root regeneration were noticed on node explants grown on WPM enriched with 1.0 mg. l-1 NAA and 2.0 mg. l-1 BA